2016
DOI: 10.3389/fmicb.2016.00910
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Biomolecular Composition Plays a Potential Role in the Host Type II Resistance to Fusarium Head Blight in Wheat

Abstract: Fusarium head blight (FHB) is a serious disease of wheat worldwide. Cultivar resistance to FHB depends on biochemical factors that confine the pathogen spread in spikes. Breeding for cultivar resistance is considered the most practical way to manage this disease. In this study, different spectroscopy and microscopy techniques were applied to discriminate resistance in wheat genotypes against FHB. Synchrotron-based spectroscopy and imaging techniques, including focal plane array infrared and X-ray fluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 59 publications
1
38
1
Order By: Relevance
“…Fourier transform infrared (FTIR) spectroscopy has become an established method for phenotyping traits associated with stress response, such as identifying cell wall biochemical markers associated with frost damage in spring wheat seeds (Xin et al ), resistance to Fusarium head blight in spring wheat (Lahlali et al , ), selection of superior barley ( Hordeum vulgare L.) cultivars by endosperm protein quality (Liu and Yu ) or differences in grain feed quality for livestock (Walker et al ). On a tissue‐specific level, FTIR spectroscopy can be used to localize total lignin, protein, cellulose, carbohydrates and lipid distributions at spatial resolutions of 1–20 μm (Vijayan et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Fourier transform infrared (FTIR) spectroscopy has become an established method for phenotyping traits associated with stress response, such as identifying cell wall biochemical markers associated with frost damage in spring wheat seeds (Xin et al ), resistance to Fusarium head blight in spring wheat (Lahlali et al , ), selection of superior barley ( Hordeum vulgare L.) cultivars by endosperm protein quality (Liu and Yu ) or differences in grain feed quality for livestock (Walker et al ). On a tissue‐specific level, FTIR spectroscopy can be used to localize total lignin, protein, cellulose, carbohydrates and lipid distributions at spatial resolutions of 1–20 μm (Vijayan et al ).…”
Section: Introductionmentioning
confidence: 99%
“…This could also result from variations in cell wall composition, before or after infection, in these species. Indeed, variations in cell wall composition during F. graminearum infection have been already described between susceptible and resistant wheat cultivars (Lahlali et al ., ). A final explanation could be the pattern of anther extrusion of the wheat variety used in this study, Apogee.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies suggest cell‐wall lignification to be an important component of FHB resistance in moderately resistant wheat genotypes and have concluded that FTIR‐based markers can be used to differentiate genotypes (Atanasova‐Penichon et al, ; Gunnaiah & Kushalappa, ; Lahlali et al, ; Lahlali et al, ). In contrast, our study did not find any consistent results for some important bipolymeric compounds such as cellulose, pectin, and xylan.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the small spectral changes in the fingerprint region (1,800–600/cm), a second derivative spectroscopy technique was employed using the Savitzky–Golay algorithm (nine smoothing points). The FTIR peaks for the various bipolymeric compounds (Table ) were assigned using the Quick Peaks routine in OriginPro software version 9.1 (OriginLab Coorporation, MA, USA) using the settings described in Lahlali et al (). Quantitative data were measured for important biopolymers such as lignin, pectin, cellulose, and xylan by integrating the area under the specific bands using OriginPro software (Table ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation